Soul Map Atlas: A Design-Science Framework Integrating Bazi, Numerology, Human Design, and Javanese Primbon with AI-Supported Self-Reflection in the Age of Digital Confession - Novia Angelina Zuraidy (Eduvest - Journal of Universal Studies, 2026)
Individuals are increasingly disclosing emotional struggles to AI chatbots, yet current systems remain largely reactive and lack the narrative structure needed to support long-term identity clarity, particularly amid growing identity fragmentation in hyperconnected digital environments. In response to this gap, the present study aims to design and evaluate an AI-augmented, birth-based identity framework called Soul Map Atlas, which integrates BaZi, Numerology, Human Design, and Javanese Primbon with adaptive AI reflection to transform unstructured emotional disclosure into coherent, lifelong self-reflection. Following a Design Science Research approach, the study derives its design principles from a synthesis of identity theory, AI-mediated disclosure literature, and symbolic-system scholarship, articulates a Context–Agency–Mechanism–Outcome (CAMO) framework, and designs a three-module artefact consisting of Birth Essence, Symbolic Integration Engine, and AI Reflection Module. The prototype is evaluated qualitatively through a two- to three-week interaction phase followed by 30-minute interviews, with the resulting data analysed using thematic, cross-case, and convergence analysis. The findings show that participants experienced combining stable, culturally grounded symbolic anchors with psychologically safe, non-deterministic AI dialogue as supportive of interpretive resonance, emotional safety, and a stronger sense of narrative continuity, although birth-time uncertainty and the absence of expert review remain limitations of the study. Overall, Soul Map Atlas offers a new category of AI–symbolic reflective artefact with implications for life coaching, digital wellbeing tools, and culturally inclusive identity support, and it warrants further longitudinal and expert-reviewed evaluation.